Autism, interventions and parent training - Booth, Nichola; Gallagher, Stephen; Keenan, Mickey (Psichologija, 2018)
Worldwide, the prevalence rates of autism are increasing. This review looks at the additional stressors that parenting a child with autism can bring, including psychological distress and mental health difficulties. With the difficulties associated with the autism diagnosis and additional demands on the parents, research has shown that parent training, which helps teach parents new skills, may be advantageous. This review also looks at the most commonly used interventions that parents might avail of in order to acquire new skills, and it examines whether they are based in science, pseudoscience or anti-science. Utilizing best practice from evidence-based research, parents can be successfully trained to teach new skills across a variety of different domains. The advantages and disadvantages of one-on-one training sessions versus group training events, as well as the different components that contribute to each, are discussed. A number of training packages are discussed, including Behavioral Skills Training, video modelling and manualized training packages. We conclude that there is substantial evidence showing that packages with behavioral underpinnings are more effective for children with autism. Autism awareness and education is simply not enough – educate the parents using evidence-based practice to help effectively educate the children